Eighteen years of the medical scientist training program at Hacettepe University - Erdener, Şefik Evren; Özön, Alev; Ertuğrul, Aygün; Dalkara, Turgay (Acta Medica, 2024)
Objective: Medical Scientist Training Program (MSTP) combining acquisition of both MD and PhD degrees, was implemented in 2003 at Hacettepe University. The purpose of this report is to evaluate the program outcomes by assessing the graduates from the first 18 years of the program. Materials and Methods: A web survey was conducted with the 37 participants who graduated between 2009-2020. Data were analysed using descriptive statistical methods. Results: About half of the graduates were found to devote a considerable amount of time to scientific research. Although nine participants do not perform any physician duties, about a quarter of graduates concomitantly pursue scientific as well as clinical activities. This implies that the program’s primary goal, to train clinician-scientists in both MD and PhD curriculums have been achieved. 90% of graduates completed their residency in 24 different clinical disciplines. 40% of the graduates have already achieved faculty status at universities in Turkey or abroad. Academic performance indicators of MSTP graduates including the number of publications and citations in leading databases and the number of grants received were notably high. Conclusion: This study reveals the role of the MSTP at Hacettepe University towards education of highly qualified clinicians with academic and scientific activities.